Bridging the Gap: Parent and Child Perspectives of Living With Cerebral Visual Impairments - Goodenough, Trudy; Pease, Anna; Williams, Cathy (Frontiers in Human Neuroscience, 2021)
Cerebral Visual Impairment (CVI) is an umbrella term which includes abnormalities in visual acuity, or contrast sensitivity or colour; ocular motility; visual field and the conscious and unconscious filtering or processing of visual input. Children with CVI have specific needs and problems relating to their development from infancy to adulthood which can impact on their wellbeing. Recent research indicates complexities of living with CVI but there remains limited information of the full impact of CVI on families’ everyday lives. The qualitative interviews reported here explored families’ experiences to discover the impact of CVI on all aspects of everyday life. Parents and children (aged 6-18) were invited to participate in semi-structured interviews, either face to face, by phone or video call between January 2018 - February 2019. Topics covered everyday practicalities of living with CVI, focusing on challenges and what worked well at school and home. Interviews were audio-recorded and subject to thematic analysis to look for patterns across the data. Twenty families took part in interviews, with eight children/young people within those families contributing interviews of their own. Four themes were developed from the interviews: (1) Assessment and understanding implications of CVI, (2) Education, (3) Family life, (4) Psychological wellbeing and quality of life. The interviews provide valuable insight into the impact of living with CVI and highlight the need for more awareness of the condition among professionals in both health and education settings.